Protein assembly and DNA looping by the FokI restriction endonuclease - Catto, Lucy E. (Oxford University Press, 2006)
The FokI restriction endonuclease recognizes an asymmetric DNA sequence and cuts both strands at fixed positions upstream of the site. The sequence is contacted by a single monomer of the protein, but the monomer has only one catalytic centre and forms a dimer to cut both strands. FokI is also known to cleave DNA with two copies of its site more rapidly than DNA with one copy. To discover how FokI acts at a single site and how it acts at two sites, its reactions were examined on a series of plasmids with either one recognition site or with two sites separated by varied distances, sometimes in the presence of a DNA-binding defective mutant of FokI. These experiments showed that, to cleave DNA with one site, the monomer bound to that site associates via a weak protein–protein interaction with a second monomer that remains detached from the recognition sequence. Nevertheless, the second monomer catalyses phosphodiester bond hydrolysis at the same rate as the DNA-bound monomer. On DNA with two sites, two monomers of FokI interact strongly, as a result of being tethered to the same molecule of DNA, and sequester the intervening DNA in a loop.